Modelling farming system dynamics in High Nature Value Farmland under policy change - Ribeiro, Paulo Flores; Santos, José Lima; Bugalho, Miguel N; Santana, Joana; Reino, Luís; Beja, Pedro; Moreira, Francisco (Agriculture, Ecosystems & Environment, 2014)
Abstract Understanding the factors driving changes in farm management is needed for designing policies and subsidy schemes to protect High Nature Value Farmland (HNVF). We describe farming system dynamics in HNVF of southern Portugal, between 2000–2002 and 2008–2010, encompassing a period of major policy transformations introduced by the reform of the Common Agricultural Policy (CAP) of the European Union in 2003. We also assess how farming system dynamics was modulated by structural, biophysical and policy factors constraining agricultural options. Farming systems changed in about 40% of the farmed area during the period of study. Overall, there was a marked transition from arable systems to either specialized livestock or permanent crop systems, involving major declines in the traditional system of dry cereal rotations and sheep grazing. Transitions were influenced by farm size, soil quality and coverage by open oak woodlands, while there was little effect of agri-environment schemes and legal regulations specifically targeted to support the traditional farming system. Despite these changes, agricultural intensity remained essentially stable, though there was a marked decline in land-use heterogeneity with likely negative impacts on biodiversity. Observed changes agree with ex-ante impact assessments of the CAP reform in Iberian cereal steppes, which suggested that decoupling of payments from production could promote shifts from the traditional cereal–fallow–sheep system towards specialized livestock grazing systems. Effectively protecting HNFV may thus require a better integration of horizontal policies and agri-environment schemes.
From Duplicate 1 ( Modelling farming system dynamics in High Nature Value Farmland under policy change - Ribeiro, Paulo Flores; Santos, José Lima; Bugalho, Miguel N.; Santana, Joana; Reino, Luís; Beja, Pedro; Moreira, Francisco )
Keywords: Agri-environment schemes; Biodiversity conservation; CAP reform; Farming systems; High Nature Value Farmland

Forest fuel management as a conservation tool for early successional species under agricultural abandonment: The case of Mediterranean butterflies - Verdasca, Maria João; Leitão, Ana Sofia; Santana, Joana; Porto, Miguel; Dias, Susana; Beja, Pedro (Biological Conservation, 2012)
In cultural landscapes there are often negative biodiversity consequences of agricultural abandonment and subsequent scrub and forest encroachment, due to homogenization and the loss of early-successional habitats. The common forestry practice of removing understory vegetation to prevent ﬁre hazard (fuel management) probably has the side-effect of ameliorating these consequences, but it is uncertain whether it effectively restores habitats for early-successional species. Here we examine the inﬂuence of time since fuel management and management frequency on butterﬂy assemblages, using a chronosequence of cork oak (Quercus suber) stands spanning about 70 years. Overall species richness increased immediately after management and abundances peaked about 2–3 years later, while both declined thereafter for about 10–20 years to pre-disturbance levels. Richness and abundances were also much higher in recurrently managed stands. Most life history groups showed successional trends similar to the overall species richness and abundances, though consistent positive effects of fuel management were only observed for species with univoltine life cycle, herbaceous layer feeding, larval overwintering, and intermediate body size. Individual species were largely associated with recent and recurrent management, though a few specialists occurred most often in undisturbed stands. These ﬁndings suggest that fuel management at <10 years intervals is strongly positive for butterﬂy assemblages in landscapes under land abandonment. However, to maintain the overall forest biodiversity it is critical that patches of undisturbed habitat are also retained at the landscape scale.
Keywords: Disturbance ecology; Ecological succession; Forest management; Landscape mosaics; Mediterranean butterﬂy assemblages

Long-term responses of Mediterranean birds to forest fuel management - Santana, Joana; Porto, Miguel; Gordinho, Luís; Reino, Luís; Beja, Pedro (Journal of Applied Ecology, 2012)
1. Mechanical management of forest fuels is increasingly used in the Euro-Mediterranean region in response to the abandonment of traditional agroforestry and the concurrent increase in fire hazard. Although fuel management may have positive side effects for biodiversity, its long-term impacts remain largely unknown. 2. We used a 70-year post-management chronosequence to investigate the influence of time since fuel management and management frequency on bird assemblages in cork oak Quercus suber forests. 3. Fuel management strongly affected bird species richness, abundances and assemblage composition, with rapid changes often occurring during the first 10–20 years, followed in the next decades by a slow convergence to pre-management levels. 4. In winter, overall species richness and abundance, and that of frugivores and shrub foragers, were negatively affected by recent and recurrent management, only recovering in stands unmanaged for >50 years. In spring, insectivore abundance and the richness and abundance of shrub foragers declined immediately following management, increased to a maximum about 20 years later, and declined thereafter. Breeding granivores and ground foragers were the only groups that benefitted from fuel management. There were no overall effects on species of conservation concern, although a few species with unfavourable status benefitted from fuel management. 5. Synthesis and applications. Our study confirmed that mechanical fuel management has positive effects on some early-successional bird species of conservation concern, although its effects were limited. These benefits should be compared with the strong negative impacts on key bird species such as wintering frugivores, which play a pivotal role in ecosystems by promoting seed dispersal. To reconcile the positive and negative aspects, fuel management should be used to create heterogeneous mosaics of forest patches encompassing a range of sizes (10–100 ha) and successional stages of understorey vegetation, including stands undisturbed for >50 years. This management strategy will likely maintain conditions for a wide range of species with contrasting ecological requirements while also reducing fire hazard.
Keywords: Disturbance ecology; Ecological succession; Fire risk; Forest management; frugivores; Landscape mosaics; Mediterranean bird assemblages